Insights into the plankton community seasonal variations in a finer scale of the Bohai Sea: biodiversity, trophic linkage, and biotic-abiotic interplay - Zhao, Yanchu; Wang, Chaofeng; Wang, Xiaoyu; Wang, Weicheng; Zhang, Tiancheng; He, Jianwu; Shi, Wenhui; Shi, Yafeng; Hu, Zihang; Zhou, Xushen (Frontiers in Marine Science, 2024)
Plankton play an indispensable role in the biogeochemical processes of marine ecosystem. However, unraveling the intricate interactions among biodiversity, trophic linkages, and biotic-abiotic interplay between phytoplankton-zooplankton remains a significant challenge. Here, we conducted field studies in the neritic area of the Bohai Sea during autumn 2023 and spring 2024 to explore seasonal variations. Our analysis revealed a sharp decline in trophic interactions across phytoplankton and zooplankton, with an abundance ratio in autumn 2023 being 5.5 times higher than in spring 2024.Additionally, dominant plankton species (Y ≥ 0.02) exhibited obvious differences between the two seasons, with higher species diversity observed in autumn. Moreover, each dominant zooplankton species had distinct preferred food items in both seasons, with Rhizosolenia setigera being favored by Noctiluca scintillans and Acartia pacifica.Furthermore, a multivariate biota-environment analysis indicated that each dominant plankton species had unique correlation with specific environmental parameters, highlighting how plankton can fully exploit external environmental conditions to survive in seasonal variations. Ultimately, our findings emphasize significant seasonal dynamics and provide a solid foundation for assessing the potential impacts of environmental changes on plankton in coastal marine realm.